'It's not really about the food, it's also about food': urban collective action, the community economy and autonomous food systems at the Groningen Free Café. Issue 2 (3rd May 2020) - Ulug, Ciska; Trell, Elen-Maarja
ABSTRACT: The Free Café is a citizen-driven collective in the city of Groningen, the Netherlands that serves a free meal biweekly, using food that would otherwise be thrown away. While principally attempting to create a space where financial pressures and social status are lifted, the group also works to raise awareness about the environmental and societal impacts of food. Using Gibson-Graham's community economies (CE) lens to analyse the Free Café, this paper aims to understand how urban citizen collectives are organised and governed, to better facilitate local action in food initiatives. Through participant observation and in-depth interviews, this research focuses on the daily practices, interactions, organisation and challenges surrounding the Free Café, to draw lessons about urban collective action and CE. Though findings indicate internal conflicts and contradictions, through sharing its vision and opportunities, the café is found to be valuable to food-waste awareness-raising and experimentation towards sustainable post-capitalist societies.